Segmentation-Guided Dual-Backbone Fusion for Robust Early Cancer Detection in Heterogeneous Medical Imaging - Nafei, Amirhossein; Chen, Shu-Chuan (Management Analytics and Social Insights, 2026)
Early detection of lung, liver, and colorectal cancers is clinically decisive because outcomes are strongly stage-dependent, yet early malignant lesions remain intrinsically difficult to identify in routine imaging due to small size, low contrast, ambiguous boundaries, partial-volume effects, and motion artifacts. Although deep learning has achieved strong performance in medical image classification and segmentation, early-stage detection under heterogeneous acquisition conditions is still limited by two structural failure modes: discriminative cues can be diluted by dominant normal anatomy when models are not explicitly guided to relevant regions, and single-backbone feature extractors can amplify inductive bias and become brittle under scanner/protocol shifts. To address these challenges, this paper proposes a segmentation-guided dual-backbone fusion architecture for robust and auditable early cancer detection across CT, MRI, and X-ray modalities. A U-Net–based module generates a probabilistic region-of-interest mask that enables ROI-focused learning via soft gating or ROI cropping, ensuring that representation learning concentrates on clinically meaningful tissue even in “needle-in-a-haystack” conditions. The ROI-focused image is then processed in parallel by two complementary encoders, ResNet and EfficientNet, and their deep embeddings are fused using Deep Feature Concatenation to reduce reliance on any single network’s failure modes and improve robustness to domain shift. The system outputs both calibrated malignancy probabilities and interpretable ROI evidence, enabling structured error attribution that separates localization failures from downstream classification failures. A reproducible synthetic evaluation protocol is further provided to demonstrate reporting practice and deployment-aligned assessment, including overall performance, size-stratified early-lesion sensitivity, domain-shift robustness, segmentation reliability indicators, and calibration measures. The proposed framework thus delivers a practical architecture blueprint that integrates robustness, interpretability, and auditability as first-class objectives for early cancer detection in heterogeneous real-world imaging settings.